Children's Environmental Health Indicators in Australia - J. Leith Sly; Sophie E. Moore; Fiona Gore; Marie Noel Brune; Maria Neira; Paul Jagals; Peter D. Sly (Ubiquity Press, 2016)
Background: Adverse environmental exposures in early life increase the risk of chronic disease but do not attract the attention nor receive the public health priority warranted. A safe and healthy environment is essential for children's health and development, yet absent in many countries. A framework that aids in understanding the link between environmental exposures and adverse health outcomes are environmental health indicators-numerical estimates of hazards and outcomes that can be applied at a population level. The World Health Organization (WHO) has developed a set of children's environmental health indicators (CEHI) for physical injuries, insect-borne disease, diarrheal diseases, perinatal diseases, and respiratory diseases; however, uptake of steps necessary to apply these indicators across the WHO regions has been incomplete. A first indication of such uptake is the management of data required to measure CEHI. Objectives: The present study was undertaken to determine whether Australia has accurate up-to-date, publicly available, and readily accessible data on each CEHI for indigenous and nonindigenous Australian children. Findings: Data were not readily accessible for many of the exposure indicators, and much of the available data were not child specific or were only available for Australia's indigenous population. Readily accessible data were available for all but one of the outcome indicators and generally for both indigenous and nonindigenous children. Although Australia regularly collects data on key national indicators of child health, development, and well-being in several domains mostly thought to be of more relevance to Australians and Australian policy makers, these differ substantially from the WHO CEHI. Conclusions: The present study suggests that the majority of these WHO exposure and outcome indicators are relevant and important for monitoring Australian children's environmental health and establishing public health interventions at a local and national level and collection of appropriate data would inform public health policy in Australia.